2022
DOI: 10.1186/s12935-022-02695-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis evasion via long non-coding RNAs in colorectal cancer

Abstract: Long non-coding RNA (LncRNA) is a novel and diverse class of regulatory transcripts that are frequently dysregulated in numerous tumor types. LncRNAs are involved in a complicated molecular network, regulating gene expression, and modulating diverse cellular activities in different cancers including colorectal cancer (CRC). Evidence indicates that lncRNAs can be used as a potential biomarker for the prognosis and diagnosis of CRC as they are aberrantly expressed in CRC cells. The high expression or silencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 164 publications
0
11
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are RNA sequences of about 200 nucleotides that play important roles in the regulation of multiple biological activities, including cell proliferation, differentiation, autophagy, and apoptosis. Accumulating evidence shows that the impairment of lncRNA regulation can lead to the development of chemoresistance and metastasis in many types of cancers, including ovarian cancer [ 3 , 36 , 37 , 38 , 39 ]. Different from lncRNAs, microRNAs (miRNAs) are smaller (16–30 nucleotides) noncoding RNAs that can regulate gene expression by targeting specific 3′-untranslated regions (3′-UTR) of target mRNA.…”
Section: Metformin As Regulator Of Cancer Cell Progression and Resist...mentioning
confidence: 99%
See 1 more Smart Citation
“…Long non-coding RNAs (lncRNAs) are RNA sequences of about 200 nucleotides that play important roles in the regulation of multiple biological activities, including cell proliferation, differentiation, autophagy, and apoptosis. Accumulating evidence shows that the impairment of lncRNA regulation can lead to the development of chemoresistance and metastasis in many types of cancers, including ovarian cancer [ 3 , 36 , 37 , 38 , 39 ]. Different from lncRNAs, microRNAs (miRNAs) are smaller (16–30 nucleotides) noncoding RNAs that can regulate gene expression by targeting specific 3′-untranslated regions (3′-UTR) of target mRNA.…”
Section: Metformin As Regulator Of Cancer Cell Progression and Resist...mentioning
confidence: 99%
“…Different from lncRNAs, microRNAs (miRNAs) are smaller (16–30 nucleotides) noncoding RNAs that can regulate gene expression by targeting specific 3′-untranslated regions (3′-UTR) of target mRNA. Both lncRNAs and miRNAs regulate important cell processes and have been used as markers in many cancerous and non-cancerous diseases [ 36 , 37 , 39 , 40 , 41 , 42 , 43 ]. Importantly, these two types of noncoding RNAs are not independent of each other, but there is a cross-talk in the regulation of their expression that allows lncRNAs to regulate miRNA expression and vice versa [ 40 ].…”
Section: Metformin As Regulator Of Cancer Cell Progression and Resist...mentioning
confidence: 99%
“…Recent studies demonstrated that some transcripts that are annotated as lncRNAs actually encode for small proteins and that lncRNAs can be processed into small ncRNAs such as miRNAs or piRNAs [ 198 , 199 , 200 ]. LncRNAs can exert oncogenic or tumor suppressor functions affecting different biological processes such as cell proliferation, cell death and drug resistance [ 201 , 202 , 203 ]. LncRNAs can be secreted into the circulation system via exosomes or bound to RBPs.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…[69][70][71]. Limitations of tumor biomarker-based detection in clinical cases derive from not discovering all the mutations and pathways involved in oncogenesis; as well as the mechanisms that allow the tumor to evade the immune system response, as data show that activation of oncogenesis pathways leads to immune system impairment [3,72,73]. Significant effort will be needed in the coming years to define and validate biomarkers that allow patient selection for personalized cancer management [74][75][76][77].…”
Section: Antigen-associated Biomarkersmentioning
confidence: 99%